ANALISIS KETERCAPAIAN KUNJUNGAN ANC DI WILAYAH KERJA UPTD PUSKESMAS TELAGA PULANG - Winda, Iska; Lisda Handayani; Puji Lestari, Yayuki (LPPM Universitas Sari Mulia, 2024)
Background: Maternal Mortality Rate (MMR) is one of the global targets of the Sustainable Development Goals (SDGs), aiming to reduce MMR to 300 per 100,000 live births by 2030. The coverage of antenatal care (ANC) visits in Central Kalimantan Province from 2016 to 2020 has shown a decline. In 2019, the K4 coverage was 84.5%, decreasing to 81.64% in 2020, and slightly increasing to 88.1% in 2021. Meanwhile, the K6 service coverage in 2021 was 63% nationally and 63.4% in Central Kalimantan Province. The importance of ANC visits has not yet become a top priority for many pregnant women in Indonesia. Objective: To analyze the achievement of ANC visits among pregnant women in the working area of the Telaga Pulang Health Center (UPTD Puskesmas Telaga Pulang). Method: This study used a quantitative analytical correlational research method with a cross-sectional approach. The population consisted of 233 individuals. Sampling was conducted using purposive sampling, with a total sample of 45 people. Data analysis was carried out using univariate and bivariate tests. Results: Based on the univariate analysis, out of 45 pregnant women, 24 (53.3%) lived more than 15 km from the health service, 26 (57.8%) accessed health services via river routes, 32 (71.1%) did not receive support from their husbands, 40 (88.9%) received support from health workers, and 32 (71.1%) did not achieve the expected number of ANC visits. Keywords: Achievement, ANC Visits, Health Center (Puskesmas)